Social Cost Bias, Probability Bias, and Self-Efficacy as Correlates of Behavioral Action in Social Anxiety. Issue 2 (March 2018) - Lee, Carol S.; Hayes-Skelton, Sarah A.
The present study investigated the role of social cost bias, probability bias, and self-efficacy as correlates of behavioral action in a nonclinical sample of 197 individuals, using a series of vignettes and self-report measures. The findings indicated that, as hypothesized, social cost bias, probability bias, and self-efficacy were associated with social anxiety. While social anxiety was associated with behavioral action, the three cognitive factors were associated with behavioral action above and beyond the contribution of social anxiety. However, contrary to the hypothesis, self-efficacy was the only cognitive factor directly associated with behavioral action when all variables were in the model. This information has implications for potential methods and target mechanisms for increasing client engagement with exposures and behavioral experiments in treatments for social anxiety.